2023
DOI: 10.1097/ju.0000000000003645
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Low-grade Intermediate-risk Nonmuscle-invasive Bladder Cancer With UGN-102 ± Transurethral Resection of Bladder Tumor Compared to Transurethral Resection of Bladder Tumor Monotherapy: A Randomized, Controlled, Phase 3 Trial (ATLAS)

Sandip M. Prasad,
William C. Huang,
Neal D. Shore
et al.

Abstract: We also thank the patients and their families and caregivers for volunteering to participate in this trial. Editorial support for the manuscript was provided by Mary Susan Prescott of Prescott Medical Communications Group (Chicago, Illinois).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…However, most of the hydrogel systems that have been used for the treatment of malignant bladder tumors, and there are few reports on their use for the treatment of benign bladder diseases such as IC/BPS. [71][72][73] However, in this study, we innovatively applied decellularized SIS tissue as a hydrogel drug delivery system and selected HA, which has proven clinical efficacy, as the drug component to develop the first novel acellular matrix/HA thermosensitive composite hydrogel for the treatment of IC/BPS, which showed excellent performance. Meanwhile, due to its advantages of temperature sensitivity, biocompatibility, slow drug release and bacteriostatic properties, it can be used in the future to treat various bladder diseases such as overactive bladder syndrome, urinary tract infection and bladder carcinoma by carrying different drug components.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the hydrogel systems that have been used for the treatment of malignant bladder tumors, and there are few reports on their use for the treatment of benign bladder diseases such as IC/BPS. [71][72][73] However, in this study, we innovatively applied decellularized SIS tissue as a hydrogel drug delivery system and selected HA, which has proven clinical efficacy, as the drug component to develop the first novel acellular matrix/HA thermosensitive composite hydrogel for the treatment of IC/BPS, which showed excellent performance. Meanwhile, due to its advantages of temperature sensitivity, biocompatibility, slow drug release and bacteriostatic properties, it can be used in the future to treat various bladder diseases such as overactive bladder syndrome, urinary tract infection and bladder carcinoma by carrying different drug components.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, adjuvant intravesical instillations of either chemotherapy or bacillus Calmette-Guérin should be delivered in intermediate- and high-risk patients (and even in low-risk patients not treated with early instillation). We found that these recommendations were not followed by the majority of the patients included in the trial by Prasad et al 1 The article does not show any final pathology results, and this renders interpretation of the results challenging. While it is undeniably intriguing to observe the superiority of the proposed approach when compared to TURBT alone, we humbly suggest that we should not overlook the established standard of care for the treatment of nonmuscle-invasive bladder cancer.…”
mentioning
confidence: 82%
“…To the Editor: We read with interest the article by Prasad et al comparing the effects of chemoablation by intravesical instillations of a mitomycin-based gel and transurethral resection (TURBT) in patients with low-grade intermediate-risk nonmuscle-invasive bladder cancer recently published in The Journal of Urology ® . 1 While we commend the authors for embarking on a prospective randomized trial, we are afraid that the design of the study renders interpretation of the results difficult. According to international guidelines, low-risk bladder cancer patients should receive an early instillation of a chemotherapeutic agent at the end of TURBT.…”
mentioning
confidence: 99%
“…The trial evaluated the efficacy and safety of intravesical chemoablation with UGN-102, a novel reverse thermal hydrogel, containing 75 mg of MMC in 56 mL admixture. The reverse thermal properties of UGN-102 allow the administration of MMC as a liquid with subsequent conversion to a semi-solid gel, allowing for contact with the bladder for 4 to 6 hours, the gel slowly disintegrates and is urinated ( 9 ).…”
mentioning
confidence: 99%
“…Furthermore, the estimated probability of DFS 15 months after randomization indicated 72% for the UGN-102 arm and 50% for the TURB arm. In the UGN-102 arm, the most frequently observed adverse events included dysuria (30%), micturition urgency (18%), nocturia (18%), and pollakiuria (16%) without meaningfully impacting the quality of life (as per EORTC-QLQ-NMIBC24) ( 9 ).…”
mentioning
confidence: 99%